A self-assembling graphene oxide coating for enhanced bactericidal and osteogenic properties of poly-ether-ether-ketone - Huang, Run; Gu, Yingjian; Yuan, Yeju; Wang, Yunxiao; Pan, Yusong; Li, Bo; Ren, Geliang; Huang, Lei; Xie, Yinghai (Frontiers in Bioengineering and Biotechnology, 2024)
Poly-ether-ether-ketone (PEEK) is a biomedical plastic that can be used for orthopaedic implant, but it still suffers from poor antibacterial properties and bioactivity. In this study, PEEK was sulphonated with the obtained porous structure adsorbing graphene oxide (GO). Surface microstructure/property of the original PEEK, sulfonated PEEK (named SPEEK) and GO-grafted PEEK (named GO-SPEEK) were characterized, the results revealed that the GO-SPEEK surface possesses a 3D porous structure exhibiting superior hydrophilicity to the original PEEK. Although the SPEEK was shown to possess antimicrobial properties against both Escherichia coli and Staphylococcus aureus, the bactericidal effect was even more significant for GO-SPEEK, at about 86% and 94% respectively. In addition, the in-vitro simulated-body-fluids immersion and cell experiments indicated that the GO-SPEEK had much better HA-precipitation induction capacity and cell-material interactions (eg. cell adhesion, proliferation, osteo-differentiation and extracellular matrix minerilization). Furthermore, the tensile test revealed that the mechanical properties of the PEEK were maintained after surface modification, as the GO-SPEEK owned comparable values of elastic modulus and tensile strength compared to PEEK. Our investigation had sought a method to simultaneously endow PEEK with both good antimicrobial properties and bioactivity as well as mechanical properties, providing a theoretical basis for developing high-performance orthopedic implants in clinic.